Impact of secondary spontaneous pneumothorax in chronic fibrosing interstitial lung disease: Pneumothorax in chronic ILD - Yamakawa, Hideaki; Tsukahara, Yuta; Sato, Shintaro; Ohta, Hiroki; Kida, Gen; Nakamura, Tomohiko; Nishizawa, Tomotaka; Kawabe, Rie; Oba, Tomohiro; Akasaka, Keiichi; Amano, Masako; Kuwano, Kazuyoshi; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
BACKGROUND: Secondary spontaneous pneumothorax (SSP) in interstitial lung disease (ILD) may influence prognosis of any ILD, and SSP onset predicts poor outcome in idiopathic pulmonary fibrosis (IPF). Recently, progressive fibrosing ILD (PF-ILD) has rapidly acquired importance.OBJECTIVES: We hypothesized that the prognostic influence of SSP may be strongly affected in PF-ILD patients not limited to those with IPF.METHODS: We retrospectively surveyed and collected data from the patients hospitalized for SSP from January 2016 to June 2020. PF-ILD was defined as the following occurring within 24 months before SSP develops: relative decline in %forced vital capacity (FVC) ≥10% or two of the following: relative decline in %FVC between 5% and 10%, worsening respiratory symptoms, or increased extent of fibrosis on high-resolution computed tomography.RESULTS: We analyzed 32 patients hospitalized for SSP in ILD. This study comprised 18 patients with PF-ILD and 14 patients with non-PF-ILD. PF-ILD patients had lower body mass index (BMI) and %FVC. No significant differences in survival regarding follow-up period from the time of ILD diagnosis and hospitalization for SSP were observed between the PF-ILD and non-PF-ILD patients. Older age and lower BMI at were significant predictors of mortality by multivariate Cox regression analysis. ROC analysis showed BMI ≤17.8 kg/m2 to reliably predict poor prognosis.CONCLUSIONS: Regardless of whether patients have PF-ILD, lower BMI in patients with ILD places them at higher risk of developing SSP and prognosis is poor if SSP develops. Therefore, clinical management of physique is important to improve the prognosis of ILD patients.